Digital Watermarking Technique on Fingerprint Image - Chugh, Nisha (My University, 2015)
In this age of automated world, the protection of data is of utmost importance. Digital watermarking is one of the probable solution along with steganography for claiming the ownership. While in steganography, data is always hidden but in watermarking, it can be visible or invisible. Digital watermarking is a technique of hiding the digital watermark, which is a low energy signal, in the image, video or audio signal, in a blind or non-blind way. This dissertation presents a Discrete Wavelet Transform (DWT) and Discrete Cosine Transform (DCT) based blind watermarking technique that securely embeds a letter image in the fingerprint image to enhance the security level. DCT, DWT and Different levels of DWT are compared in terms of Peak Signal to noise ratio and fitness factor. The analysis of watermarked image under the salt & pepper and JPEG compression attacks has been carried out to find out the robustness of the system. DWT gives much better result than DCT and in the DWT, as the level of transform increases, imperceptibility of the watermarked image is increased in such a way that it can cheat the human vision easily on the other hand robustness get decreased, fitness factor of the extracted watermark is not good enough as it was in the previous level. It is concluded that there has to be a tradeoff between the robustness and imperceptibility of the watermark. Apart from imperceptibility and robustness, average elapsed time for embedding and extraction has also been compared between DCT and various levels of DWT and results shows that DCT take more time than DWT and time get reduced as the level of DWT increases.
M.E. (Electronic Instrumentation and Control Engineering)
Keywords: DWT; DCT; PSNR; MSE